Pengaruh substitusi tepung daun kelor (moringa oleifera) terhadap daya terima, tekstur, daya simpan, dan jumlah total kapang pada snack bar cadelo - Suryani, Dian; Kustiani, Ai; Adyas, Atikah (Published by: Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2025)
Background: Anemia among adolescent girls remains a nutritional problem that needs to be addressed. Anemia is a condition characterized by a decrease in red blood cell mass, characterized by decreased hemoglobin levels, hematocrit levels, and the number of red blood cells in the bloodstream. Purpose: To analyze the effect of Moringa oleifera leaf flour substitution on the acceptability, texture, shelf life, and total mold count of Cadelo snack bars. Method: The study used a Completely Randomized Design (CRD) with four treatment levels (F0 = 0%, F1 = 5%, F2 = 10%, F3 = 15%) and two replications. Organoleptic assessments were conducted by 25 panelists using a hedonic scale of 1–5. Texture was measured using a CT-3 Texture Analyzer, while total mold analysis was conducted on days 0 and 15 of room temperature storage. Results: Formulation F1 (5% moringa) obtained the highest score (p < 0.001) for all sensory attributes. The hardness of F1 increased significantly compared to F0 (p < 0.05), but remained within the acceptable limits for consumption. The total mold count in F1 was lower than the control on day 0 (p < 0.05) and remained stable until day 15. Conclusion: The addition of 5% moringa leaf flour has been shown to improve sensory and textural quality and has the potential to suppress mold growth during storage. Keywords: Moringa Leaf Flour; Shelf Life; Substitution. Pendahuluan: Kondisi anemia terhadap remaja putri masih menjadi permasalahan gizi yang perlu diatasi. Anemia merupakan suatu kondisi ketika terjadi penurunan jumlah massa eritrosit yang ditandai oleh menurunnya kadar hemoglobin, hematokrit, dan jumlah eritrosit dalam sirkulasi darah. Tujuan: Untuk menganalisis pengaruh substitusi tepung daun kelor (Moringa oleifera) terhadap tingkat penerimaan, tekstur, daya simpan, dan jumlah total kapang pada produk snack bar Cadelo Metode: Desain penelitian menggunakan Rancangan Acak Lengkap (RAL) dengan empat tingkat perlakuan (F0 = 0%, F1 = 5%, F2 = 10%, F3 = 15%) dan dua kali ulangan. Penilaian organoleptik dilakukan oleh 25 panelis menggunakan skala hedonik 1–5. Tekstur diukur dengan alat Texture Analyzer CT-3, sedangkan analisis total kapang dilakukan pada hari ke-0 dan ke-15 penyimpanan suhu ruang. Hasil: Formula F1 (5% kelor) memperoleh skor tertinggi (p < 0.001) untuk seluruh atribut sensoris den. Kekerasan pada F1 meningkat secara signifikan dibandingkan F0 (p < 0.05), namun masih dalam batas kenyamanan konsumsi. Total kapang pada F1 lebih rendah daripada kontrol pada hari ke-0 (p < 0.05) dan tetap stabil hingga hari ke-15. Simpulan: Penambahan 5% tepung daun kelor terbukti dapat meningkatkan kualitas sensoris dan tekstur, serta berpotensi menekan pertumbuhan kapang selama masa penyimpanan. Kata Kunci: Daya Simpan; Subtitusi; Tepung Daun Kelor.